Research on Detection Technology of 235U Enrichment and Loading Uniformity for Nuclear Fuel Rods - Gu, Mingfei; Huang, Dagui; Yu, Dongbao; Tang, Hui; Zhu, Yongli (Frontiers in Energy Research, 2021)
To ensure that fuel rods operate in nuclear reactors safely and reliably, UO2 pellets with different enrichment levels of 235U in the same production line are manufactured in batches and divisionally managed to avoid confusion or the potential misloading of UO2 pellets with different enrichment levels. At the same time, nondestructive tests for their enrichment levels and loading uniformity and all UO2 pellets must be nondestructively tested during production. By studying the enrichment detection mechanism of the UO2 pellets of 235U, the design of an integral standard rod was carried out, and a single integral standard rod was used to achieve the calibration of the enrichment measurement curve, as well as the detection and calibration of abnormal pellets. This study undertook a comparison test of 235U enrichment between the neutron activation method and the array multi-probe passive method. The test results showed that the array multi-probe passive method had higher detection efficiency and equal accuracy.